Pengaruh Kualitas Layanan terhadap Kepuasan Mahasiswa dengan Pendekatan Higher Education Performance (HedPERF) di Jurusan Arsitektur Fakultas Teknik Universitas Brawijaya - Susilowati, Enik; Mindarti, Lely Indah; Domai, Tjahjanulin (Jurnal Ilmiah Administrasi Publik, 2022)
This purpose of this study was to determine the effect of service quality on student satisfaction in Department of Architecture, Faculty of Engineering, Brawijaya University Malang. The research used a Higher Education Performance (HedPERF) measurement scale. The dimensions of service quality used in this study are the theory of Abdullah (2006a & 2006b) which consists of Non-Academic, Academic, Reputation, Access and Program Issues. The research method used quantitative method with associative approaches. The research utilized questionnaire surveys with Probability Sampling techniques and Stratified Random Sampling collection techniques. Then the data obtained were tested using multiple linear regression analysis and IPA (Importance Performance Analysis). The results showed a significant effect simultaneously between Non Academic, Academic, Reputation, Access, and Program Issues variables on student satisfaction.